Digital Transformation in the Drugstore Industry: A Case Study - Demaj, Esmir; Hysa, Xhimi; Sadaj, Abdyl (European Journal of Economics and Business Studies, 2020)
The phenomenon of digital transformation has become widespread and relevant in a variety of industries. This era of transformation has changed the traditional business models. However, the implementation of digital services in the drugstore industry, has developed at a relatively slow pace. The core of the drugstore business model has remained product-centric and therefore pharmacies are still in an experimental phase when it comes to offering more than the traditional products. Digital services play a vital role in such occasions because they accelerate the process, making it easier to implement. This research, using the case of an innovative pharmacy located in Albania, will give an outlook of the challenges faced by this industry on daily basis and the opportunities for innovation, how important is for the costumer the value added to the products they purchase, and also an overview of what the process of digitalization might look like for this industry.Key Words: Drugstore Industry, Digital transformation, Digitization, Pharmacy “Daja”
Keywords: Words: Drugstore Industry, Digital transformation, Digitization, Pharmacy “Daja”